The Political Economy of Corruption Law Enforcement in Indonesia - Ridwan Arifin; Auliya Rochman; Muhammad Ikram Nur Fuady (JUSTISIA GLOBAL EDUKASI, 2026)
Corruption remains one of the most persistent challenges affecting governance, public trust, and economic development in Indonesia. Although extensive legal reforms and institutional mechanisms have been introduced to combat corruption, enforcement outcomes often reveal inconsistencies and political contestation. This study examines corruption law enforcement in Indonesia through a political economy and Critical Legal Studies perspective. Using a normative-critical methodology, the research analyzes the interaction between legal institutions, political interests, and economic power structures in shaping anti-corruption enforcement. The findings indicate that corruption law enforcement operates within a complex environment characterized by competing political agendas, institutional rivalries, and unequal access to power. Legal processes frequently reflect broader political and economic dynamics rather than functioning as entirely autonomous mechanisms of justice. The study demonstrates that selective enforcement, institutional dependence, and political intervention may undermine the effectiveness and legitimacy of anti-corruption initiatives. Furthermore, anti-corruption discourse often emphasizes legal compliance while overlooking structural factors that facilitate corrupt practices. From a critical legal perspective, corruption is not merely an individual legal violation but also a manifestation of broader governance and power relations. The research argues that sustainable anti-corruption reform requires strengthening institutional independence, enhancing public accountability, and addressing structural inequalities that enable the concentration of political and economic influence. The study concludes that effective corruption law enforcement depends on transforming both legal institutions and the political-economic conditions within which they operate. These findings contribute to critical legal scholarship by highlighting the interconnected relationship between law, power, and governance in contemporary Indonesia.